2016
DOI: 10.1093/geront/gnv689
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Sedentary Behavior Among Socially Engaged Older Adults

Abstract: These findings have implications for use of terminology in policy and public health strategies targeting sedentary time reduction in older adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
61
0
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(80 citation statements)
references
References 34 publications
10
61
0
9
Order By: Relevance
“…Four focus groups were conducted at separate locations on separate dates at the same time of year (December). The methodology for this study has been described in detail elsewhere [10] . All methods and communications were approved by the Research Ethics Board at the University of Ontario Institute of Technology.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Four focus groups were conducted at separate locations on separate dates at the same time of year (December). The methodology for this study has been described in detail elsewhere [10] . All methods and communications were approved by the Research Ethics Board at the University of Ontario Institute of Technology.…”
Section: Methodsmentioning
confidence: 99%
“…The original purpose of the focus groups was simply to understand the perceptions of older adults regarding sedentary behaviour; these data have been published [10] . In addition, the investigators wanted to learn more to better understand how to reduce sedentary time among older adults.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many participants considered reducing their own sedentary behaviour to be of value, although those reporting relatively high activity levels appeared unconvinced that they would receive additional benefit on top of the benefits of being active. McEwan et al (2017) found that older adults frequently used specific activities to define sedentary behaviour, for example, watching television, knitting and computer use. This is consistent with the present findings, whereby participants were able to speak accurately about sedentary behaviour in an isolated context when drawing upon such specific examples of behaviours.…”
Section: Main Findingsmentioning
confidence: 99%
“…À semelhança do que foi verificado nas funções cognitivas, parece que diferentes comportamentos sedentários podem ter consequências distintas na dimensão social dos idosos. Nesse sentido, as evidências indicam que os idosos percecionam benefícios sociais quando realizam comportamentos sedentários que considerem significativos (Mcewan, Tam-Seto, & Dogra, 2016). Desta forma, parece que determinados comportamentos sedentários (e.g., uso de computador, jogar bingo, estar sentado em conversa social) são positivos para a saúde psicossocial dos idosos (O´Neill & Dogra, 2016).…”
Section: Funções Sociaisunclassified